People are worse at detecting fake news in their foreign language - Muda, Rafał; Pennycook, Gordon; Hamerski, Damian; Białek, Michał (Journal of experimental psychology. Applied, 2023)
Across two preregistered within-subject experiments ( = 570), we found that when using their foreign language, proficient bilinguals discerned true from false news less accurately. This was the case for international news (Experiment 1) and more local news (Experiment 2). When using a foreign (as opposed to native) language, false news headlines were always judged more believable, while true news headlines were judged equally (Experiment 2) or less believable (Experiment 1). In contrast to past theorizing, the foreign language effect interacted neither with perceived arousal of news (Experiment 1) nor with individual differences in cognitive reflection (Experiments 1 and 2). Finally, using signal detection theory modeling, we showed that the negative effects of using a foreign language were not caused by adopting different responding strategies (e.g., preferring omissions to false alarms) but rather by decreased sensitivity to the truth. (PsycInfo Database Record (c) 2023 APA, all rights reserved).